Therapeutic and preventive effect of feed additives on the state of periodonts of rats with experimental dysbiosis - Levitsky, A.; Markov, A.; Pupin, T.; Selivanskaya, I.; Lapinskaya, A. (Journal of Education, Health and Sport, 2021)
Aim. Determine the therapeutic and prophylactic effect of feed additives on the condition of the periodontium in case of dysbiosis. Methods. As feed additives, we used flour from pea straw (FPS), oilcake from ordinary (high-linoleic) sunflower seeds (OOS) and oilcake from high-oleic sunflower seeds (OHOS), which were added to the composition of feed for rats in an amount of 10% instead of the same amount of grain wheat. The duration of feeding was 18 days. Experimental dysbiosis was reproduced using the antibiotic lincomycin. The activity of urease, lysozyme, catalase, elastase and the content of malondialdehyde (MDA) were determined in the gums of rats. Results. An increase in the level of urease, elastase, MDA and a slight decrease in the activity of lysozyme and catalase were found in rats with dysbiosis. The consumption of FPS and OOS had little effect on the biochemical parameters of the gums; however, the consumption of OHOS significantly reduced the activity of elastase, the level of MDA and normalized the level of urease. Conclusion. Under conditions of dysbiosis, periodontitis develops, which can be prevented by consuming high-oleic sunflower oilcake.